Black Lives Matter: An Evening with Co-founder Alicia Garza - Garza, Alicia
From its roots as an online rallying call protesting police shootings of young people of color, Black Lives Matter is a vibrant social justice movement with global reach. Co-founder Alicia Garza shares the story of transforming a Twitter hashtag into real-life activism. This event positions the Black Lives Matter movement within its larger political, social and cultural landscape, and how it amplifies the ways everyday people can most effectively enact social change. Co-sponsored by the University Library, Dean of Students, Office of Undergraduate Studies, College of Education, Health & Human Services, Department of Sociology, Department of Social Sciences, College of Humanities, Arts, Behavioral and Social Sciences. This video is *only* available to CSUSM students, staff, and faculty. You must have a CSUSM user name and password to view it. Copy the following URL into your preferred browser window to view: https://hermes.csusm.edu/Mediasite/Play/451cf4d0deda463091cdb85bede629711d